The Role of Zakat in Helping Communities : A Study on BAZNAS Scholarship and the Renewal of the BAZNAS-AIU Agreement in Supporting Scholarship Recipients - Tri Hartati; Fikriyyah Fikriyyah; Mohamad Mokhlis B Ahmad Fuad; Farid Septian; Muhammad Syukron Amin (International Journal of Zakat, 2025)
This study investigates the role of BAZNAS (Badan Amil Zakat Nasional) scholarship on the personal growth, academic stress and educational outcomes of recipients at AIU (Albukhary International University). A sample of BAZNAS AIU scholarship recipients was analyzed using regression analysis. Data were gathered through surveys, with 52 BAZNAS AIU recipients as respondents. The results showed that mentorship, provided as part of the scholarship program, has a significant positive impact on personal growth, with 12.8% of the variance explained by this factor. Financial support, however, does not have a statistically significant negative effect on academic stress, suggesting that other factors may play a role in managing students' pressures. Additionally, institutional collaboration between BAZNAS and AIU was found to significantly improve educational outcomes, accounting for 33,3% of the variance. The findings reveal that mentorship and institutional collaboration all play significant roles in influencing personal growth and educational outcomes. However, financial support has a negative effect on academic stress, highlighting the need for comprehensive support mechanisms beyond financial aid.